Amphiphilic ligand modified gold nanocarriers to amplify lanthanide loading for ultrasensitive DELFIA detection of Cronobacter. Issue 1 (20th November 2019) - Fang, Hao; Li, Xiangmin; Leng, Yuankui; Huang, Xiaolin; Xiong, Yonghua
Abstract : Thiolated ethylenediaminetetraacetic acid and thiolated acylhydrazine-terminated ligands modified gold nanoflowers as amplified nanocarriers to increase the Ln 3+ labeling ratio for improving the sensitivity of traditional DELFIA. Abstract : Conventional dissociation-enhanced lanthanide (Ln 3+ ) fluoroimmunoassays (DELFIAs) using Ln 3+ chelate-labeled antibodies as molecular probes exhibit limited sensitivity because of their relatively low Ln 3+ labeling ratio per biomolecule. Herein, we applied gold nanoflowers (AuNFs) as amplified nanocarriers to increase the Ln 3+ labeling ratio in a single molecular binding event for improving the sensitivity of traditional DELFIA. Two thiolated amphiphilic ligands (thiolated ethylenediaminetetraacetic acid (EDTA) and thiolated acylhydrazine-terminated ligands), consisting of a hydrophobic alkane chain, oligo(ethylene glycol) unit, and functional terminal of the EDTA or acylhydrazine group, were designed for the surface modification of AuNFs. The resultant ligand-coated AuNFs exhibited dual functions of Ln 3+ chelation via the EDTA group and oriented attachment of antibodies via the acylhydrazine group. By utilizing 80 nm AuNFs as amplified carriers, we demonstrated that the maximum Eu 3+ loading amount reached 1.07 × 10 4 Eu 3+ ions per AuNF, which is approximately two to three orders of magnitude higher than that of traditional molecular probes, thereby amplifying the luminescence signal and enhancing the sensitivity of DELFIA. By combining a magnetic-mediated sandwich-type DELFIA method, the designed amplified AuNF nanoprobes achieved an ultrasensitive luminescence detection of Cronobacter muytjensii with a limit of detection (LOD) of 1.2 × 10 2 cfu mL −1 in a powdered infant formula. This LOD value was ca. 230-fold lower than that of the traditional colorimetric immunoassay. The designed signal amplification strategy using bifunctional ligand-modified AuNFs as enhanced Ln 3+ nanocarriers provided a huge potential for building various ultrasensitive luminescence immunoassays for in vitro biodetection.